An islet maturation media to improve the development of young porcine islets during in vitro culture. Issue 3 (3rd May 2020) - Lau, Hien; Corrales, Nicole; Rodriguez, Samuel; Luong, Colleen; Zaldivar, Frank; Alexander, Michael; Lakey, Jonathan R. T.
ABSTRACT: Background: The use of pancreata from pre-weaned piglets has the potential to serve as an unlimited alternative source of islets for clinical xenotransplantation. As pre-weaned porcine islets (PPIs) are immature and require prolonged culture, we developed an islet maturation media (IMM) and evaluated its effect on improving the quantity and quality of PPIs over 14 days of culture. Methods: PPIs were isolated from the pancreata of pre-weaned Yorkshire piglets (8–15 days old). Each independent islet isolation was divided for culture in either control Ham's F-10 media (n = 5) or IMM (n = 5) for 14 days. On day 3, 7 and 14 of culture, islets were assessed for islet yield, isolation index, viability, insulin content, endocrine cellular composition, differentiation of beta cells, and insulin secretion during glucose stimulation. Results: In comparison to control islets, culturing PPIs in IMM significantly increased islet yield. PPIs cultured in IMM also maintained a stable isolation index and viability throughout 14 days of culture. The insulin content, endocrine cellular composition, and differentiation of beta cells were significantly improved in PPIs cultured in IMM, which subsequently augmented their insulin secretory capacity in response to glucose challenge compared to control islets. Conclusions: Culturing PPIs in IMM increases islet yield, isolation index, viability, insulin content, endocrine cellular composition, differentiation of endocrine progenitor cells toward beta cells, and insulin secretion. Due to the improved islet quantity and quality after in vitro culture, the use of IMM in the culture of PPIs will assist to advance the outcomes of clinical islet xenotransplantation.